Microplastic exposure represses the growth of endosymbiotic dinoflagellate Cladocopium goreaui in culture through affecting its apoptosis and metabolism. (April 2020) - Su, Yilu; Zhang, Kaidian; Zhou, Zhi; Wang, Jierui; Yang, Xiaohong; Tang, Jia; Li, Hongfei; Lin, Senjie
Abstract: Microplastics are widespread emerging marine pollutants that have been found in the coral reef ecosystem. In the present study, using Cladocopium goreaui as a symbiont representative, we investigated cytological, physiological, and molecular responses of a Symbiodiniaceae species to weeklong microplastic exposure (Polystyrene, diameter 1.0 μm, 9.0 × 10 9 particles L −1 ). The density and size of algal cells decreased significantly at 7 d and 6–7 d of microplastic exposure, respectively. Chlorophyll a content increased significantly at 7 d of exposure, whereas Fv/Fm did not change significantly during the entire exposure period. We observed significant increases in superoxide dismutase activity and caspase3 activation level, significant decrease in glutathione S-transferase activity, but no change in catalase activity during the whole exposure period. Transcriptomic analysis revealed 191 significantly upregulated and 71 significantly downregulated genes at 7 d after microplastic exposure. Fifteen GO terms were overrepresented for these significantly upregulated genes, which were grouped into four categories including transmembrane ion transport, substrate-specific transmembrane transporter activity, calcium ion binding, and calcium-dependent cysteine-type endopeptidase activity. Thirteen of the significantly upregulated genes encode metal ion transporter and ammonium transporter, and five light-harvesting protein genes were among the significantly downregulated genes. These results demonstrate that microplastics can act as an exogenous stressor, suppress detoxification activity, nutrient uptake, and photosynthesis, elevate oxidative stress, and raise the apoptosis level through upregulating ion transport and apoptotic enzymes to repress the growth of C. goreaui . These effects have implications in negative impacts of microplastics on coral-Symbiodiniaceae symbiosis that involves C. goreaui . Graphical abstract: Image 1 Highlights: The growth and density of algal cells were repressed by microplastic exposure. Microplastics declined detoxification activity, nutrient uptake, and photosynthesis. Microplastics raised oxidative stress, apoptosis level and ion transport.